Pengembangan Instrumen Tes untuk Mengukur Kemampuan Berpikir komputasional Siswa dalam Pembelajaran Matematika: Sebuah Tinjauan Sistematis - Meliana Sukma Desti; Putri Nur Malasari (Universitas Dr. Soetomo, 2026)
Abstract The integration of computational thinking (CT) into mathematics is highly strategic due to the cognitive overlap between the two fields. However, the validity and reliability of its measurement instruments remain major challenges. This study aims to map the development of CT test instruments in mathematics through a Systematic Literature Review (SLR) of 8 empirical articles (2021-2025). The novelty of this research lies in the critical analysis of psychometric quality and the characteristics of domain-specific mathematics instruments. The results indicate a dominance of development at the elementary school level (50%). Critical findings reveal significant variations in reliability, where low coefficients (0.27 and 0.33) indicate the limitations of classical statistics in measuring multidimensional CT. The conclusion emphasizes the urgency of shifting to modern psychometric analysis (Rasch/IRT) and expanding instrument development to higher education levels to ensure the continuity of student cognitive measurement from basic to advanced levels. Keywords: Computational Thinking, Test Instrument, Mathematics Learning, Systematic Literature Review, Assessment. Abstrak Integrasi berpikir komputasional (CT) dalam matematika sangat strategis karena adanya tumpang tindih kognitif antara dua bidang. Namun, validitas dan reliabilitas instrumen pengukuran masih menjadi tantangan utama. Penelitian ini bertujuan memetakan pengembangan instrumen tes CT dalam matematika melalui metode Systematic Literature Review (SLR) terhadap 8 artikel empiris (2021-2025). Kebaruan penelitian ini terletak pada analisis kritis kualitas psikometrik dan karakteristik instrumen spesifik domain matematika. Hasil menunjukkan dominasi pengembangan pada jenjang SD (50%). Temuan kritis mengungkap variasi reliabilitas signifikan, di mana koefisien rendah (0,27 dan 0,33) mengindikasikan keterbatasan statistik klasik dalam mengukur CT yang multidimensi. Simpulan menekankan urgensi pergeseran ke analisis psikometrik modern (Rasch/IRT) serta perluasan pengembangan instrumen pada jenjang pendidikan tinggi guna menjamin kesinambungan pengukuran kognitif siswa dari level dasar hingga tinggi. Kata Kunci: Berpikir komputasional, Instrumen Tes, Pembelajaran Matematika, Systematic Literature Review, Asesmen.